ANALISIS MAKNA GERAK TARI JEPIN LANGKAH GRESIK PANTAI KELURAHAN SUNGAI JAWI DALAM KOTA PONTIANAK KALIMANTAN BARAT - Agisna Niswatana; Imma Fretisari; Asfar Muniir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe background of this research are to  know and to understand deeper about the form of the performance of JepinLangkahGersikPantai dance, including the range of motion, accompaniment music, cosmetology, and the clothes Also, upper and under design, and the place to show. The methodology of this research is descriptive qualitative method with choreography approach. The results of this research are 1. JepinLangkahGersikPantai at Pontianak West Kalimantanis represented the life of the people who live near the beach. 2. JepinLangkahGersikPantai is divided into three categories those are first movement (pantai) second movement (nyusorarus), last movement (nyusorgelombang). 3. The numbers of the dancers should be in even numbers and consist of men and women. 4. The instruments of this dance are beruas, violin, accordion, and gambus. 5. JepinLangkahGersikPantai dance is using realistic cosmetics. 6. The uniform of the women’s dancers consist of telokbelange clothes, corakinsangstuff,  kembanggoyang stuff and the last is flowers. 7 the uniform of the men’s dancers are consist of telokbelanga clothes and corakinsang pants. Keywords:Dance Steps in, Jepin Gresik Pantai,The Meaning of